2016
DOI: 10.1590/0103-6440201600596
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Periodontal Disease, Insulin Resistance, Salivary Cortisol, and Stress Levels during Pregnancy

Abstract: Pregnancy is a period involving important metabolic changes that enable the maintenance of the mother's health and development of the fetus. This study aimed to assess the relationship among periodontal disease, insulin resistance, salivary cortisol concentration and level of perceived stress in pregnant women. This was a cross-sectional study. The sample comprised 96 pregnant women between the fifth and seventh month of pregnancy registered at the Basic Health Units of the Unified Health System (SUS). The per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
13
0
4
Order By: Relevance
“…A similar condition was also observed in relation to oral health, where the data showed that a negative classification of disease results in a greater possibility of elderly persons also considering their general health to be poor (OR =1.92). This is unsurprising, as the oral cavity is part of the individual and is today considered to have a direct influence on overall health, contributing to high levels of quality of life and health perception [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…A similar condition was also observed in relation to oral health, where the data showed that a negative classification of disease results in a greater possibility of elderly persons also considering their general health to be poor (OR =1.92). This is unsurprising, as the oral cavity is part of the individual and is today considered to have a direct influence on overall health, contributing to high levels of quality of life and health perception [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…It was seen that most of the pregnant women (48%) were between 21 and 30 years old, while the minority (19%) were between 31 and 40 years. A study by Moimaz et al (13) presented a mean age of 24.7 years while that of Seraphim et al (8) presented a mean age of 26.18 years for the 96 pregnant women they evaluated. The mean ages in these studies were very close to those of this present study.…”
Section: Discussionmentioning
confidence: 94%
“…Gingivitis can be considered the main oral disease affecting women in the gestational period, due to an increase in the concentration of female sex hormones, and leads to exacerbated gingival inflammation (2,5,8,12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, o estresse parece alterar o processo inflamatório dificultando a cicatrização devido ao fato de deprimir as funções dos neutrófilos e linfócitos, o que facilita a invasão e bacteriana. [21][22][23][24] Além disso, o segundo fator está relacionado à diminuição da microcirculação gengival e do fluxo salivar. 17,20 A resistência do tecido hospedeiro pode ser alterada por mecanismos que atuam por meio do sistema nervoso autônomo e de glândulas endócrinas, resultando em elevação dos níveis de cortisol e catecolaminas.…”
Section: Introductionunclassified